DAMPAK AGLOMERASI KAWASAN PERDAGANGAN DAN JASA ANTASARI BANDAR LAMPUNG TERHADAP SOSIAL DAN EKONOMI BERDASARKAN PERSEPSI MASYARAKAT - Rahman, Yudha; Thitipat; Prasetya, Dwi Bayu; Martin Lutherking (Jurnal Perencanaan dan Pengembangan Kebijakan, 2025)
This study analyzes the social and economic impacts of agglomeration in the Antasari Trade and Service Corridor in Bandar Lampung, based on local community perceptions. As a rapidly developing urban zone, the corridor has transformed from a residential area into a hub of commercial and service activities since 2015. Using a quantitative deductive approach, data were collected through surveys and field observations involving 100 respondents from four surrounding sub-districts. Statistical inference and scalogram analysis were applied to assess the significance and intensity of impacts. The results indicate that agglomeration has led to notable changes in daily activities, consumer behavior, entrepreneurial interest, and comfort levels due to increased traffic congestion, noise, and informal street trading. Economically, while it has not significantly increased average income, the development has enhanced job opportunities, business prospects, and land value. The social impact was found highest in Kedamaian, whereas the economic impact peaked in Tanjung Baru. The findings highlight the dual nature of agglomeration and provide policy insights for sustainable and socially equitable urban planning in growing metropolitan areas. The recommendation from this study is the need for government regulations regarding the development of trade and service areas to minimize negative impacts in the future.